Faktor Kejadian Cacingan pada Balita Stunting di Kecamatan Pamulihan Kabupaten Sumedang - Elba, Fardila (Sehat MasadaJurnal, 2021)
According to Riskesdas in Indonesia, helminthiasis is also still common, especially in children with a prevalence in 2013 of 22.6%. The impact that occurs if a toddler is continuously infected with worms, one of which is stunting. This study aims to compare the incidence of helminthiasis in toddlers (12-59 months) stunting and non-stunting in Cijeruk Village, Pam taken by the total sampling method and as many as 120 toddlers included in the control group taken by the proportionate stratified random sampling method. Research instruments using questionnaires and laboratory examinations.The results of a comparative study of the incidence of helminthiasis showed that there were 2 respondents (1.1%) positive had a helminthiasis and 178 (%) had no helminthiasis. The conclusion of this study is that there is no relationship between the incidence of helminthiasis on the incidence of stunting in Cijeruk Village, which is seen based on statistical tests (p = 1,000).